Nilai Humanisme dalam Novel Rembulan Tenggelam di Wajahmu Karya Tere Liye dan Implikasinya dalam Pembelajaran Teks Novel - Monica, Sahara; Zulfikarni, Zulfikarni (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
Humanism in modern times, people often experience an identity crisis due to the ideologies that emerge in modern society. There are many problems in modern times caused by humans themselves. Humanism is a matter related to human life and the good and bad of human association must be an example that something good will be rewarded with good deeds and vice versa. The purpose of this study is to describe the value of humanism and the implications of the value of humanism in the novel Rembulan Tenggelam Di Wajahmu by Tere Liye. This type of research is qualitative in the form of written or spoken words from people and observed behaviors such as book literature and internet sites. The method used is descriptive which is done by collecting data in the form of words, pictures, and not numbers. The results obtained in this study were found by researchers related to the value of humanism in the novel Rembulan Tenggelam Di Wajahmu by Tere Liye, which explains one by one the indicators of the value of freedom, the value of cooperation, the value of willing to sacrifice, the value of caring, the value of helping, and the value of solidarity.